2010
DOI: 10.1534/genetics.109.112086
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Modulates Ubx Protein Function inDrosophila melanogaster

Abstract: The Drosophila Hox gene Ultrabithorax (Ubx) produces a family of protein isoforms through alternative splicing. Isoforms differ from one another by the presence of optional segments-encoded by individual exons-that modify the distance between the homeodomain and a cofactor-interaction module termed the ''YPWM'' motif. To investigate the functional implications of Ubx alternative splicing, here we analyze the in vivo effects of the individual Ubx isoforms on the activation of a natural Ubx molecular target, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 107 publications
2
38
0
Order By: Relevance
“…Based on our data and on previous reports we think that there may be three different responses when either the Ia or IVa proteins are expressed: (1) some Ubx targets, such as decapentaplegic in the visceral mesoderm (at least as to its anterior repression) and those needed to specify the embryonic cuticle, probably respond similarly to the different Ubx proteins (Busturia et al, 1990;Mann and Hogness, 1990;Subramaniam et al, 1994;Gebelein et al, 2002;Reed et al, 2010); (2) other targets, such as sal, wg and ara in the haltere disc, as well as others needed to repress wing development and promote haltere development, are more efficiently regulated by isoform Ia than IVa, but if the levels of the latter are increased, a similar regulation is achieved; and (3) the expression of dpp in the posterior visceral mesoderm (Reed et al, 2010) or of targets needed to specify the segmental pattern in the embryonic peripheral nervous system (Mann and Hogness, 1990;Subramaniam et al, 1994), are differently controlled by proteins Ia and IVa, independently of their levels of expression.…”
Section: Regulation Of Ubx Targets By Different Ubx Isoformssupporting
confidence: 58%
See 1 more Smart Citation
“…Based on our data and on previous reports we think that there may be three different responses when either the Ia or IVa proteins are expressed: (1) some Ubx targets, such as decapentaplegic in the visceral mesoderm (at least as to its anterior repression) and those needed to specify the embryonic cuticle, probably respond similarly to the different Ubx proteins (Busturia et al, 1990;Mann and Hogness, 1990;Subramaniam et al, 1994;Gebelein et al, 2002;Reed et al, 2010); (2) other targets, such as sal, wg and ara in the haltere disc, as well as others needed to repress wing development and promote haltere development, are more efficiently regulated by isoform Ia than IVa, but if the levels of the latter are increased, a similar regulation is achieved; and (3) the expression of dpp in the posterior visceral mesoderm (Reed et al, 2010) or of targets needed to specify the segmental pattern in the embryonic peripheral nervous system (Mann and Hogness, 1990;Subramaniam et al, 1994), are differently controlled by proteins Ia and IVa, independently of their levels of expression.…”
Section: Regulation Of Ubx Targets By Different Ubx Isoformssupporting
confidence: 58%
“…Although Dll expression in Ubx MX17 animals, or in embryos with high levels of the IVa isoform, has not been detailed, high levels of this protein repress the formation of Keilin's organs, which is driven by Dll expression (Mann and Hogness, 1990). We note that Ubx MX17 adults have abnormalities in metathoracic legs and the A1 (Busturia et al, 1990; and this report), in the development of A1 and A2 larval abdominal muscles (Reed et al, 2010) and are not as healthy as wild-type flies (Subramaniam et al, 1994), suggesting that isoform IVa may be less efficient than isoform Ia in controlling many Ubx targets, not just those making a haltere. In conclusion, we think that the particular architecture of cis-regulatory regions in each Ubx target may account for the inclusion of each gene in one of these three categories, so a specific research may be needed for each case.…”
Section: Regulation Of Ubx Targets By Different Ubx Isoformsmentioning
confidence: 73%
“…Further genetic work on the PNS showed that indeed Ubx-IVa cannot substitute functionally for other isoforms to promote normal development of the PNS (Subramaniam et al, 1994). Recent studies using the Drosophila UAS/Gal4 system further demonstrated the impact of Ubx alternative splicing on the activation of Ubx target genes during embryogenesis (Reed et al, 2010) and on the ability of Ubx to control the morphology and underlying gene networks of adult appendage development (de Navas et al, 2011).…”
Section: Review Development 140 (19) Review Development 140 (19)mentioning
confidence: 99%
“…Development 140 (19) (Bantignies et al, 2011;Tolhuis et al, 2011) Mouse: (Noordermeer et al, 2011;Yu et al, 1995;Yu et al, 1998) Transcriptional regulation Yes Yes Drosophila: (reviewed by Alexander et al, 2009;Maeda and Karch, 2009;Tschopp and Duboule, 2011) Mouse: (reviewed by Alexander et al, 2009;Maeda and Karch, 2009;Tschopp and Duboule, 2011) lncRNA regulation Yes Yes Drosophila: (Petruk et al, 2006;Sanchez-Elsner et al, 2006) Mouse: Dinger et al, 2008;Wang et al, 2011) RNA processing Yes Yes Drosophila: O'Connor et al, 1988;Hatton et al, 1998;Reed et al, 2010;Thomsen et al, 2010) Mouse: (LaRosa andGudas, 1988;Benson et al, 1995;Fujimoto et al, 1998) miRNA regulation Yes Yes Drosophila: (Ronshaugen et al, 2005;Tyler et al, 2008;Stark et al, 2008;Bender, 2008;Thomsen et al, 2010) Mouse: (Yekta et al, 2004;McGlinn et al, 2009;He et al, 2011) Translational regulation Likely Yes Drosophila: (Oh et al, 1992;Ye et al, 1997) Mouse: (Brend et al, 2003;Kondrashov et al, 2011) Note that owing to space limitations only a few key references are listed here. For further details, see main text.…”
Section: Reviewmentioning
confidence: 99%
“…These observations indicate that, in the case of Dll regulation, modifying the mode of interaction does not affect DNA binding. However, the distinct DNA binding affinities displayed by Dm-UbxIa and Dm-UbxIVa on a composite Hox/Exd site (34) suggest that modifying the mode of interaction may have a different effect on other targets.…”
Section: Discussionmentioning
confidence: 99%